ByzRev 05.2023.030: Sofia Kotzabassi (Hrsg.), A Companion to the Intellectual Life of the Palaeologan Period: (Brill’s Companions to the Byzantine World 12). Leiden: Brill 2023. - Kubina, Krystina (The Byzantine Review, 2023)
Sofia Kotzabassi (Hrsg.), A Companion to the Intellectual Life of the Palaeologan Period (Brill’s Companions to the Byzantine World 12). Leiden: Brill 2023. xi+519 pp. – ISBN 978-90-04-52706-5 (€ 261.00)